A Development of Aquaponic E-Commerce System - Ng, Zhin Yen; Ab. Aziz, Ruhaya (Applied Information Technology And Computer Science, 2023)
Aquaponic is an urban farming method that promotes sustainable agriculture that is around for a long time but the knowledge of it is still at a relatively low level and the availability of aquaponic accessories is very limited. Aquaponic e-commerce system is developed to improve the availability of aquaponic accessories and increase knowledge about aquaponic for the user of the system who are customers and staffs of MEA Aquaponic PLT. The functional module of this system includes login and register, manage product, make payment, manage order, manage stock and access forum. This application is developed as a web-based system with MongoDB, React.js, Node.js and Express.js through prototyping software process model. With the development of aquaponic e-commerce system, customer can purchase aquaponic accessories and gain knowledge about aquaponic practice online. This will encourage more people to get involved in aquaponic practice and increase the sustainability of food to the world.